An Alarming Mimicry of Intra-Abdominal Infections: Acute Appendiceal Diverticulitis. (12th November 2021) - Kim, Youseung; Kesar, Varun; Grider, Douglas; Chitnavis, Maithili V.
Abstract : A 65-year-old woman presented with three days of colicky abdominal pain. Abdominal imaging illustrated small bowel enteritis, ascites in both paracolic gutters, and incidental hepatic steatosis. Although ascites fluid demonstrated high neutrophil count consistent with peritonitis and the patient received adequate antibiotics, she clinically deteriorated. Subsequent exploratory laparotomy revealed necrotic appendix and multiple intra-abdominal abscesses. Histopathology showed acute suppurative appendicitis with multiple other intact small diverticula, indicating likely perforation of inflamed appendiceal diverticula with subsequent abscess formation and abdominal peritonitis. This case highlights the importance of ascites fluid analysis and continued clinical correlation, especially in cases of rare entities with atypical presentations.